Digitalisasi SOP Pengaduan Masyarakat pada Dinas Kependudukan dan Pencatatan Sipil Kota Medan - Siahaan, Andysah Putera Utama; Parinduri, Hery Saputra; Al Fikri, Muhammad Dafa (Jurnal Pengabdian Masyarakat Berdampak, 2026)
Population administration services are one of the most important forms of public service for the community. In its implementation, the Department of Population and Civil Registration (Disdukcapil) of Medan City still faces several obstacles in managing public complaints, such as ineffective complaint handling processes, unintegrated data recording, and less optimal monitoring of complaint follow-up. These conditions can affect the quality of public services and the level of community satisfaction. This community service activity aims to implement a web-based digitalization of Standard Operating Procedures (SOP) for public complaints at the Department of Population and Civil Registration of Medan City in order to improve the effectiveness, transparency, and quality of population administration services. The implementation method was carried out through several stages, including needs analysis, system design, user training, system implementation, and monitoring and evaluation of system usage. The results of the activity show that the web-based public complaint information system is able to help the community submit complaints more easily and quickly. In addition, the system also assists Disdukcapil officers in managing complaint data, monitoring follow-up actions, and improving the efficiency of complaint services. Based on the implementation and training results, Disdukcapil employees were able to understand and operate the system properly, thereby supporting the creation of more responsive, transparent, and accountable public services. With the implementation of this digitalized public complaint SOP system, it is expected that the quality of population administration services at the Department of Population and Civil Registration of Medan City will continue to improve and support the digital transformation of information technology-based public services.